BENARKAH PASAR MODAL KITA EFISIEN? BUKTI DARI JAKARTA STOCK EXCHANGE - Dwiarso Utomo; Fuad Fuad (University of Merdeka Malang, 2008)
This study tested efficiency of market hypothesis to stock prices in Indonesia byusing two unit root tests. First, we implemented a test that could account for two structuralbreaks because of financial crisis in the underlying series. Second, we employed variance ratiotest to test the null hypothesis of random walk after adjusting for heterocedasticity. The resultsindicated that there were breaks, particularly in the intercept of the trend function. We alsofound that our heterocedastic-consistent variance ratio test documents rejected random walkhypothesis. The results somehow revealed the ambiguous results which were perhaps due toheterocedasticity in the data.